(untitled) (Journal of the College of Basic Education, 2025)
first-year middle school students from the point of view of male and female Arabic language teachers. The research was limited to male and female Arabic language teachers in schools affiliated with the General Directorate of Education in Maysan Governorate for the academic year 2023-2024. The total research sample consists of (40) male and female teachers. The researcher directed a survey questionnaire to know the reasons for spelling weakness among first-year middle school students. The question included the following: What are the reasons leading to spelling weakness among first-year middle school students? It was presented to a survey sample consisting of (20) male and female teachers, where the researcher prepared the final questionnaire that he formulated according to the teachers’ answers, and presented it to experts and specialists in Arabic language teaching methods to verify its apparent validity, and its reliability was calculated by the retest method, where its reliability level reached (0.80), then the final questionnaire was presented to the original sample consisting of (40) male and female teachers, and after statistical processing of the data - the results of the research showed that there are a number of reasons that lead to the weak achievement of first-year middle school students in the dictation subject, and in light of the results, the researcher presented a set of recommendations and suggestions